PENGARUH RAPAT ARUS ANODIZING TERHADAP NILAI KEKERASAN PADA PLAT ALUMINIUM PADUAN AA SERI 2024-T3 - Fajar Nugroho (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
Aluminum alloy AA 2024-T3 is widely applied in the aircraft industry because it has good mechanical properties such as; light weight, good conductivity and the corrosion resistance. However Aluminium 2024-T3 susceptible to wearing. One method to improve the wear resistance o f AA 2024-T3 is the anodizing process. The aims of this research to study the effect of current density and anodizing time against the hardness of aluminum alloy AA 2024-T3. The process of anodizing was carried out using 10 percent sulfuric acid solution with the current density of 1.5 Ampere per decimeters square, 3.0 Ampere per decimeters square and 4.5 Ampere per decimeters square with immersion times of 30, 40, 50 and 60 minutes. Furthermore, the surface hardness was measured by using the Vickers hardness test method. As the supporting data the composition of the test conducted, testing the microstructure, and vickers hardness test. This study shows that the surface hardness of aluminum alloy AA 2024-T3 is influenced by the current density and anodizing time with varying values. Its shows that higher current density o f the anodizing caused optimal time tends to be short. The longer anodising time it will produce greater layer of aluminum oxide.